Low Molecular Weight Polyphenols in Cork of Quercus suber (Journal of Agricultural and Food Chemistry, 1997)
Low molecular weight polyphenols were studied by HPLC in samples of cork from different trees of Spanish Quercus suber and at different industrial processing stages. Gallic, protocatechuic, vanillic, caffeic, ferulic, and ellagic acids; protocatechuic, vanillic, coniferylic, and sinapic aldehydes, and aesculetin and scopoletin were identified and quantified. Ellagic acid was the main component in all of the samples, followed by the rest of the phenolic acids, which had very much lower concentrations. Four components, caffeic, ferulic, and protocatechuic acids and vanillin, were selected as those that provided the greatest differences among the trees studied. In relation to the four industrial processing stages considered, marked differences were observed between the first two stages, stripping and first rest, and the stages after boiling. In this case, the discriminant variables were coniferaldehyde, sinapaldehyde, and ellagic acid. Keywords: Quercus suber; cork; polyphenols; phenolic acids and aldehydes; coumarins; high-performance liquid chromatography
doi: 10.1021/jf960486w